Moving from basic toward systems pharmacodynamic models 1. Issue 9 (16th May 2013) - Jusko, William J.; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract Building upon many classical foundations of pharmacology, a diverse array of mechanistic pharmacokinetic–pharmacodynamic (PK/PD) models have emerged based on mechanisms of drug action and primary rate‐limiting or turnover processes in physiology. An array of basic models can be extended to handle various complexities including tolerance and can readily be employed as building blocks in assembling enhanced PK/PD or small systems models. Our corticosteroid models demonstrate these concepts as well as elements of horizontal and vertical integration of molecular to whole‐body processes. The potential advantages and challenges in moving PK/PD toward systems models are described. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2930–2940, 2013